2019
DOI: 10.1038/s41598-019-47659-7
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer cells respond differentially to autophagy inhibition in vivo

Abstract: Autophagy has both tumor-promoting and -suppressing effects in cancer, including colorectal cancer (CRC), with transformed cells often exhibiting high autophagic flux. In established tumors, autophagy inhibition can lead to opposite responses resulting in either tumor cell death or hyperproliferation. The functional mechanisms underlying these differences are poorly understood. The present study aimed to investigate the relationship between the autophagic capacities of CRC cells and their sensitivities to auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 76 publications
6
46
0
1
Order By: Relevance
“…Additionally, Ra EA et al indicated that TRIM31 could promote Atg5/Atg7-independent autophagy in intestinal cells [51]. In addition, Lauzier A et al showed that ATG5 overexpression could promote the development of cancer in vitro [52]. In our research, the miR-155-5p mimic significantly decreased the expression of ATG5.…”
Section: Discussionsupporting
confidence: 61%
“…Additionally, Ra EA et al indicated that TRIM31 could promote Atg5/Atg7-independent autophagy in intestinal cells [51]. In addition, Lauzier A et al showed that ATG5 overexpression could promote the development of cancer in vitro [52]. In our research, the miR-155-5p mimic significantly decreased the expression of ATG5.…”
Section: Discussionsupporting
confidence: 61%
“…Is there a therapeutic window during which autophagy inhibition will be most beneficial [392,393]? What are the cellular and cancer contexts in which autophagy inhibition will be therapeutically beneficial [22,394,395,396]? Are there indirect or direct caveats to autophagy inhibition in certain cancer contexts, and how can we minimize them [395,397,398]?…”
Section: Discussionmentioning
confidence: 99%
“…ER is shown to increase NAD + levels, stimulate SIRT1, and promote autophagy [176,177]. Therefore, preventing toxic accumulation of protein or organelles and oncogenic signaling through autophagy represents another defensive influence mediated by ER-based strategies against cancer and CRC [178], although different sensitivities for autophagy inhibition in CRC have been described [179]. Importantly, contradictory implications for autophagy and SIRT1 in carcinogenesis and CRC are also found, with oncogenic or tumor suppressive functions depending on the cancer type and the particular background or tumor microenvironment [174,178,180,181].…”
Section: Fundamental Cellular and Molecular Adaptations Induced By Enmentioning
confidence: 99%